The Effect of Academic Supervision and the Quality of Early Childhood Education Teachers on the Quality of Education in South Papua Province - Waranggraini, Ludgardis Wonga; Susanti, Debie (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to analyze the effect of academic supervision and teacher quality on the quality of education in South Papua Province. The research approach uses quantitative, causal study type research (influence / cause and effect study) using survey methods. The population in this study was all teachers in ECCE schools in Merauke District. Sampling technique using porposive sampling. The number of teachers who met the criteria amounted to 77 teachers. The data collection instrument of this study used questionnaires. The variables in this study are academic supervision and teacher quality as independent variables, and education quality as a dependent variable. The data analysis technique uses multiple linear regression. The results showed that the significance value (Sig.) of academic supervision of 0.048 was smaller than the probability < of 0.05, and the significance value (Sig.) of teacher quality so that it can be concluded that there is a significant influence of academic supervision and teacher quality on the quality of education.